2017
DOI: 10.1089/met.2016.0116
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Metabolic Syndrome in Women with Severe Obesity

Abstract: In women with severe obesity, higher FFM and REE were paradoxically associated with increased rather than decreased risk of MetS, while FFM-adjusted FM was unrelated to MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…In the present study, we found that female patients had a higher prevalence of obesity than male patients (nearly double), consistent with previous studies (17,40,41). Moreover, compared to non-obese individuals, obese women had a higher proportion of hypertension, diabetes, and hyperlipidaemia, suggesting that they develop metabolic syndrome (42,43). However, in our study, we did not find that obesity had any effect on mental symptoms or cognitive function among female patients with schizophrenia, inconsistent with other research conclusions (44,45).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that female patients had a higher prevalence of obesity than male patients (nearly double), consistent with previous studies (17,40,41). Moreover, compared to non-obese individuals, obese women had a higher proportion of hypertension, diabetes, and hyperlipidaemia, suggesting that they develop metabolic syndrome (42,43). However, in our study, we did not find that obesity had any effect on mental symptoms or cognitive function among female patients with schizophrenia, inconsistent with other research conclusions (44,45).…”
Section: Discussionsupporting
confidence: 92%
“…However, based on multiple results obtained from our research group 14–19 and others, 20–23 we recently reported, in contrast with the generally purported idea, that a greater FFM could be negatively associated with insulin sensitivity and metabolic health in various populations. The dissonance between these contradictory conclusions could stem from the different ways FFM is represented in the numerous pertinent studies.…”
Section: Introductionmentioning
confidence: 59%
“…Abdominal fat accumulation, particularly visceral fat (VF) mass, contributes to worsening the dyslipidemic and hypertensive profile detected in women with impaired glucose tolerance [ 24 ]. VF accumulation is generally accompanied by insulin resistance (IR), increased release of free fatty acid by adipose tissue, and secretion of ApoB containing particles by the liver, leading to hyperlipidemia.…”
Section: Gender Differences In Metabolic Syndrome Componentsmentioning
confidence: 99%
“…These lipid changes are indicative of increased cardiovascular risk and contribute to the number of women meeting the diagnosis of MetS. Thus, monitoring and controlling waist circumference, a marker of abdominal obesity and VF accumulation, represents a key strategy to counteract the clinical consequences of MetS, especially in postmenopausal women [ 24 ].…”
Section: Gender Differences In Metabolic Syndrome Componentsmentioning
confidence: 99%